-y + -4y = -5y

y(y - 2)(y + 2)

y-4y-2-3y-2y+4y+25y+2y-4y+23y+2y+4y-25y-2

4y = 929 4y/4 = 929/4 y = 232.25

4y + 5w

3

4y + 7 = 19 ∴ 4y = 12 ∴ y = 3

0

5y

4y+y=10 5y=10 y=2

4y + 10 = 22 4y - 10 - 10 4y=12 4y 4y 4y=3

The greatest common factor in the two terms is [ 4y ].The factored form of the expression is4y (y + 7x)

assuming that the question is asking 4y = 48, y = 12

when y = 3, 8y-4y = 4y = 4*3 = 12

4y + 3 >= -94y >= -9 + -34y >= -12y >= -12/4y >= -3

4y - 5 = 7x ∴y = 7/4x + 5/4 slope = 7/4, or 1.75 4y - 5 = 7x ∴4y/7 - 5/7 = x ∴4y/7 - 5/7 = 0 ∴4y = 5 ∴y = 1.2 the y-intercept is 1.2

All you can do to factor that expression is to divide both terms by y: y2 + 4y = y(y + 4)

3x + 4y = 04y = -3xy = -0.75xy = mx + b with b being the y interceptSince: y = -0.75x + 0 , the y-intercept is 0.

Assume the expression is x = 40 - 4y, and assume we want to solve for y. Rearrange the terms to get: x - 40 = -4y y = -¼(x - 40)

If you mean 6x + 4y, then 4y=(-6x+24) y=(-6x+24)/4= y=(-3/2)x+6 b=6 If you mean 6x - 4y then -4y=(-6x+24) y=(-6x+24)/-4 y=(3/2)x-6 b=-6

x2 -y2 +4y-4=(x+y)(x-y)+4y-4

4y-9 = 15 4y = 15+9 4y = 24 y = 6

4y -2 = 6 4y = 6 + 2 4y = 8 y = 2

y = -6

3x=4y-x 4x=4y x=y